(untitled) - Mader, Sylvia S.; Sylvia S. Mader (Dubuque, IA)
Instructors consistently ask for a textbook that helps students understand the relationships between the main concepts of biology, so they are not learning facts about biology in isolation. Mader's Concepts of Biology was developed to fill this void. Organized around the main themes of biology, Concepts of Biology guides students to think conceptually about biology and the world around them. Just as the levels of biological organization flow from one level to the next, themes and topics in Concepts of Biology are tied to one another throughout the chapter, and between the chapters and parts. Combined with Dr. Mader's hallmark writing style, exceptional art program, and pedagogical framework, difficult concepts become easier to understand and visualize, allowing students to focus on understanding how the concepts are related
Keywords: Biology